Are synechiae a complication of laparotomic myomectomy?. Issue 4 (April 2018) - Capmas, Perrine; Pourcelot, Anne-Gaelle; Fernandez, Hervé
Abstract: Laparotomic myomectomy is often the only realistic solution for symptomatic women with multiple or large myomas who wish to retain their fertility. The aim of this study was to document the rate of uterine synechiae and their associated risk factors after laparotomic myomectomy. This prospective observational study took place in a teaching hospital from May 2009 to June 2014. It included all women aged 18–45 years who had laparotomic myomectomies (without diagnostic hysteroscopy at the time of surgery) for myomas and a postoperative diagnostic office hysteroscopy 6–8 weeks later. The study included 98 women with a laparotomic myomectomy and a postoperative hysteroscopic follow-up. Women with a laparotomic myomectomy for a subserosal myoma were excluded. The intrauterine adhesion rate after laparotomic myomectomy was 25.51% (25/98); 44% (11/25) of them were complex intrauterine adhesions. Opening the uterine cavity was a major risk factor for these complex adhesions, with an OR of 6.42 (95% CI 1.27 to 32.52). Office hysteroscopy could be carried out after surgery in such cases.